2006
DOI: 10.1073/pnas.0600289103
|View full text |Cite
|
Sign up to set email alerts
|

Making a virtue out of a necessity: Hurricanes and the resilience of community organization

Abstract: M ost of us these days are all too aware of the disruptive impact of hurricanes in human affairs. Yet disturbances ranging from minor local disruptions to massive large-scale catastrophes are part-and-parcel of life in most natural ecosystems (1, 2). These disturbances often provide scientific opportunities, because sometimes one learns the most about how a system functions by watching it recover after it has been kicked by a major disturbance (e.g., ref.3). Ecologists increasingly recognize that the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Despite the immediate and seemingly far reaching devastation that follows intense natural disturbances, there is an extensive literature showing that such events can ultimately generate environmental conditions favourable to the survival, growth and diversification of living organisms and ecosystems, at least as measured by species diversity [1] [7] . Recently, studies have shown parallel responses to disturbance between species and genetic diversity with variation between-sites (beta diversity) increasing and within-sites (alpha diversity) decreasing [8] [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the immediate and seemingly far reaching devastation that follows intense natural disturbances, there is an extensive literature showing that such events can ultimately generate environmental conditions favourable to the survival, growth and diversification of living organisms and ecosystems, at least as measured by species diversity [1] [7] . Recently, studies have shown parallel responses to disturbance between species and genetic diversity with variation between-sites (beta diversity) increasing and within-sites (alpha diversity) decreasing [8] [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Eastern Puerto Rico has repeatedly experienced major hurricanes during the last few decades, resulting in an ideal opportunity to assess context‐dependent effects of intense disturbances on the spatial and temporal demographics of local populations and communities (Walker et al 1991, 1996). Because global warming may increase the frequency and intensity of hurricanes in the future (Webster et al 2005), understanding the long‐term effects of successive disturbances on the resilience of ecological systems is imperative (Holt 2006, Schoener and Spiller 2006). Despite links between global warming and increasing frequency and intensity of hurricanes, this relationship likely is not linear (Holland and Bruyère 2014), such that isolating the effects of global warming from those of hurricane‐induced disturbances is especially challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The role of disturbance in molding the structure and function of ecosystems has emerged as a paradigm guiding much ecological research from theoretical (Holling, 1973;Holt, 2006;Pickett et al, 1989;Willig & Walker, 1999) and empirical (Schowalter et al, 2021;Walker et al, 1991Walker et al, , 1996Willig et al, 2007Willig et al, , 2011Willig et al, , 2021 perspectives. Tropical forests in the Greater Caribbean Basin are disturbance-mediated systems that are structured as a consequence of a longhistory of repeated, intense storms (Waide & Lugo, 1992;Walker et al, 1991Walker et al, , 1996Zimmerman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%